Investigating the factors causing and contributing to the emergence of Escherichia coli infection in some broiler chicken farms in Tartous - عفيف, آلاء; علي نيصافي ,; عبد الناصر العمر, (Latakia University Journal -Biological Sciences Series, 2024)
Escherichia coli is considered a major cause of economic losses in broiler farms, which requires investigating the most important causative factors and contributing to the emergence of its infection. In this study, 281 samples of chickens suspected of being infected with Escherichia coli were examined from 14 poultry farms spread across Tartous Governorate during a full year from 10/26/2022 to 10/2/2022. 116 samples showed positivity for infection with Escherichia coli, with a rate of 41.28%, with the highest percentage reaching 100% in Matrou (11) and Saya (12) poultry farms, then Saya (12) (13) poultry farms, where the percentage was 95 and 90%, respectively, then Al-Hamidiyeh (9). with an infection rate of 66.6%, then Khirbet al-Mu'azza (7) with 58.2%, then Marqiyah (4) with a rate of 50%, and Amrit (1) with a rate of 30.03%, while the farms Abu Afsa (2), Al-Wadi Al-Akhdar (3), Marqiyah (5), and Al-Wadi were all empty. Green (6) from injury. Some of the factors contributing to and causing infection with E. coli were investigated on the farms themselves, such as water, feed, ventilation, and the presence of diseases. The most influential and contributing factor to the emergence of E. coli infection in those farms was the presence of various diseases, especially respiratory diseases, which was evident in the poultry farms of Amrabet (1) and Marqia. (4) Khirbet al-Mu'azza (7), al-Hamidiyah (9), Matro (11), and Saya poultry farms (12)(13)(14). Then comes the second level of fodder with water in the Saya poultry farms, followed by the ventilation factor, which appeared in the Marqiyya and Khirbet al-Mu'azza poultry farms, in addition. The effect of diseases with ventilation in the poultry farms of Marqia (4) and Khirbet al-Muazza (7), and fodder with water and diseases in the poultry farms of Saya, where the different percentages of these factors contribute to infection. The highest percentage of the presence of various diseases reached 57.1%, followed by water and fodder at a rate of 21.42%, followed by ventilation at a rate of 14. 28%, which requires concerted efforts and strict adherence to biosecurity measures in broiler farms to reduce the rates of infection with E. coli and other diseases and reduce the economic losses resulting from reducing the mortality rate and the cost of treatment.